Evaluation of the status of marine plastic pollution along a tourist beach of Bay of Bengal during lockdown and post lockdown. (September 2022) - Khadanga, Mukunda Kesari; Behera, Anil Kumar; Swain, Gopal Krushna; Dora, D. Prabin; Padhi, Chinmaya Prasad; Mishra, Rajani Kanta; Pradhan, Subhasis; Barik, Subhajit; Mohanty, Pratap Kumar; Mishra, Pravakar; Patro, Shesdev
Abstract: Marine plastic pollution is a global issue that has calamitous consequences for global economy, biodiversity, human health, and the climate. A few of the studies were carried out on the Gopalpur coast and the current baseline survey was conducted during Covid-19 pandemic lockdown (April–August 2021) and post lockdown (August–September 2021).The survey was covered about 1500 m along the coast, divided into 10 equal zones of each (20 × 150 m 2 ) to collect the plastic debris based on colour, density, and weight. Plastic debris was categorized into 33 types with an average 1.276 g/m 2 during lockdown and was categorized into 34 types with an average 3.34 g/m 2 in post lockdown. The results imply that tourism has a greater impact on the beach in terms of pollution when compared with the local sources, which will have a drastic effect on the aesthetics of the beach, neighbouring turtle nesting site and indirectly on human health. Graphical abstract: Unlabelled Image Highlights: Plastic pollution increased by 2.616 folds in post lockdown than lockdown in the study area. Plastic average debris per 100 m 2 was found 127.6 g in lockdown and 333.9 g in post lockdown. Poly-bags and food wrappers were found mostly as dominant debris during post lockdown. Tourism and use of plastics have a greater impact on the beach pollution compared to local sources. The 3-R (Reduce, Recycle and Reuse) formula to be implemented to minimize plastic pollution